UNLOCKING POTENTIAL: GORONTALO'S VISION FOR CHILD-FRIENDLY URBAN DEVELOPMENT - Makalalag, Febian Nataya; Mozin, Sri Yulianty; Isa, Rusli (Universitas Negeri Gorontalo, 2024)
This study aims to determine (1) Implementation of Policies for Organizing Child Friendly Cities in Gorontalo City and (2) Factors that determine the Implementation of Policies for Organizing Child Friendly Cities in Gorontalo City from the aspects of planning, implementation, and evaluation. This research method uses a type of qualitative research, with data collection techniques used are observation, interviews, and documentation. Based on the results of research found in the field that (1) Implementation of Policies for Organizing Child Friendly Cities in Gorontalo City, researchers used three aspects in the Implementation of Policies for Organizing Child Friendly Cities in Gorontalo City, namely planning, implementation, and evaluation. The planning has been going well because of the existence of regional regulations and also the preparation of the Regional Action Plan (RAD). Implementation has been planned clearly and well because with the existence of regional regulations and the establishment of a task force which has been divided into several clusters, each relevant OPD can clearly carry out programs in the context of fulfilling children's rights. The evaluation is carried out systematically by involving several related OPDs which have been divided into several clusters to see how far the programs they have created are in fulfilling children's rights. the benefits of this evaluation will later determine the outcome of each cluster. (2) The factors that determine the implementation of child-friendly city management policies in Gorontalo City are seen from four aspects, namely communication, resources, disposition and bureaucratic structure. communication has been carried out well, with socialization and also coordination meetings. resources are fairly adequate and also the facilities and facilities are quite adequate. the disposition is good enough with technical guidance also held. There is no bureaucratic structure in procuring child-friendly city SOP